Ontogenetic development of the gastrointestinal tract of African lungfish larvae Protopterus aethiopicus (Heckel 1851): A light microscopy study. (1st September 2020) - Sserwadda, Martin; Nevejan, Nancy; Ntanzi, Ronald; Cornillie, Pieter; Van den Broeck, Wim; Van Stappen, Gilbert
Abstract: The organogenesis of the digestive system was described in the African lungfish ( Protopterus aethiopicus ) from 6 days post‐hatching (6 DPH) to 17 days post‐hatching (17 DPH) reared at 27°C. To elucidate the position of the gastrointestinal tract in relation to the neural tube, notochord and yolk sac at 6 DPH, and to the vertebral column, lungs and kidneys at 17 DPH, larvae were mapped by means of computer‐assisted 3D reconstructions starting from histological serial sections. The larvae showed a simple digestive tract, which appeared as a straight undifferentiated and closed tube at 6 DPH. Microscopical observation showed that yolk reserves were not completely depleted by 17 DPH. During the endogenous feeding period at least up to 17 DPH, the larval digestive system experienced a fast transformation with almost complete development of most digestive organs (pharyngeal teeth, intestinal vestibule, intestine and liver). Our findings suggest that, by 17 DPH, African lungfish larvae are ready to start exogenous feeding.